Molecular characterization of a wild poliovirus type 3 epidemic in The Netherlands (1992 and 1993). - Mulders, M N (1995)
An outbreak of poliomyelitis due to wild poliovirus type 3 (PV3) occurred in an unvaccinated community in The Netherlands between September 1992 and February 1993. The outbreak involved 71 patients. The aim of this study was to characterize the virus at the molecular level and to analyze the molecular evolution of the epidemic virus. Molecular analysis was carried out by sequencing the VP1/2A junction region (150 nucleotides) of 50 PV3 strains isolated in association with this outbreak and the entire VP1 gene of 14 strains. In addition, the sequence of the VP1/2A junction region of strains from geographical regions endemic for PV3 (Egypt, India, and Central Asia) was analyzed and compared with the nucleotide sequence of the epidemic strain from The Netherlands. The earliest isolate was obtained from river water sampled 3 weeks before diagnosis of the first poliomyelitis patient and was found by VP1/2A sequence analysis to be genetically identical to the strain isolated from the first patient. Sequence divergence among the strains from the epidemic in The Netherlands was less than 2%. The closest genetic similarity (97.3%) was found with an Indian isolate (New Delhi, December 1991), indicating the likely source of the virus. A more than 99% sequence similarity was found in the VP1/2A region. Finally, the sequence information was used to design primers for the specific and highly sensitive molecular detection of PV3 strains during the epidemic.